Cyclic Deformation and Stress-Strain Characteristics of 38XH3MФA Steel - Nguyen, Van Duong; Bui, Manh Cuong (Old Journal, 2018)
In this paper, the cyclic plastic behaviors such as cyclic hardening and cyclic creep of special steel garde 38XH3MФA are studied. Tensile test (uniaxial monotonic test) has been conducted to get mechanical properties of the materials. Cyclic deformation tests were carried out for specimens bearing uniaxial load over materials yield limit in cyclic tension-compression with both strain – controlled and stress – controlled methods. The obtained stress – strain loops were used to identify the cyclic hardening parameters, the Bauschinger effect and cyclic creep characteristics of the steel. The experiment results show the good mechanical properties of 38XH3MФA steel and its capability to endure cyclic deformation.